Penguatan Mutu Baca Tulis Al-Qur’an (BTA) Melalui Metode Al-Masyhuroh Berbasis Life Skill Pengolahan Limbah Ikan pada Komunitas Nelayan Tanjung Mas Semarang - Khoiri, Nur; Mustopa, Mustopa; Udaibah, Wirda (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2017)
Assistance to the community is provided in order to provide education using fast, good and correct learning methods. In addition to literacy education of the Qur'an, coastal communities who work as fish seekers on average also need to be equipped with skills (life skill). Through education and training, coastal communities will have two advantages at once, first able to study the Qur'an quickly, rightly and correctly, and both gain knowledge about fish waste processing. Devotion is done also provide life skill education (life skills) such as processing pellets / feed from fish waste. Supply provided is not limited to the training course but also helps in the management of production permits and feasibility of processing the pellet, and find opportunities in marketing the processed products.